Defense related decadienal elicits membrane lipid remodeling in the diatom Phaeodactylum tricornutum - Tanya, Sabharwal (Public Library of Science (PLoS), 2018)
Diatoms rapidly release extracellular oxylipins (oxygenated lipids) including polyunsaturated aldehydes in response to herbivory and other stresses. Oxylipins have several defenserelated activities including inhibition of reproduction in herbivores and signaling to distant diatoms. Physiological changes in diatoms exposed to varying levels of oxylipins are only beginning to be understood. In this study, Phaeodactylum tricornutum cultures were treated with sublethal concentrations of the polyunsaturated aldehyde trans,trans-2,4-decadienal (DD) to assess effects on lipid composition and membrane permeability. In cells treated with DD for 3 hr, all measured saturated and unsaturated fatty acids significantly decreased (0.46–0.69 fold of levels in solvent control cells) except for 18:2 (decreased but not significantly). The decrease was greater in the polyunsaturated fatty acid pool than the saturated and monounsaturated fatty acid pool. Analysis of lipid classes revealed increased abundances of phosphatidylethanolamine and phosphatidylcholine at 3 and 6 hr. Concomitantly, these and other membrane lipids exhibited increased saturated and monounsaturated acyl chains content relative to polyunsaturated acyl chains compared to control cells. Evidence of decreased plasma membrane permeability in DD treated cells was obtained, based on reduced uptake of two of three dyes relative to control cells. Additionally, cells pre-conditioned with a sublethal DD dose for 3 hr then treated with a lethal DD dose for 2 hr exhibited greater membrane integrity than solvent pre-conditioned control cells that were similarly treated. Taken together, the data are supportive of the hypothesis that membrane remodeling induced by sublethal DD is a key element in the development of cellular resistance in diatoms to varying and potentially toxic levels of polyunsaturated aldehydes in environments impacted by herbivory or other stresses.